Essential core competencies for health policy graduates: a multi-method consensus type study - Leila Doshmangir; Minoo Alipouri Sakha; Hakimeh Mostafavi; Neda Kabiri; Saeideh Ghaffarifar; Amirhossein Takian (BMC, 2024)
Abstract Background In light of the multi-faceted challenges confronting health systems worldwide and the imperative to advance towards development goals, the contribution of health policy graduates is of paramount importance, facilitating the attainment of health and well-being objectives. This paper delineates a set of core skills and competencies that are requisite for health policy graduates, with the objective of preparing these graduates for a spectrum of future roles, including both academic and non-academic positions. Methods The study was conducted in three phases: a scoping review, qualitative interviews and the validation of identified competencies through brainstorming with experts. In the initial phase, a scoping review was conducted on the databases. The following databases were searched: PubMed, Scopus, Web of Science and Google Scholar search engine. Additionally, the WebPages of universities offering health policy programmes were manually searched. In the second phase, 36 semi-structured interviews were conducted with students, graduates and distinguished academics from Iran and other countries. These interviews were conducted in person or via email. In the third phase, the draft version of the competencies and their associated learning objectives, derived from the preceding stages, was subjected to independent review by an expert panel and subsequently discussed. In light of the expert panel's findings, the authors undertook a subsequent revision of the list, leading to the finalization of the core competencies through a process of consensus. Results In the scoping review phase, the analysis included six studies and nine university curricula. The results of the scoping review could be classified into five domains: health system understanding, health policy research, knowledge translation, multidisciplinary work and knowledge of public health. In the second phase, six core competencies were extracted from the interviews and combined with the results of the first phase, which were then discussed by the expert panel at the third phase. The final five core competencies, derived from the brainstorming session and presented in no particular order, encompass health policy research, policy analysis, educational competencies, decision-making and multidisciplinary work. Conclusions It is essential that the curriculum is appropriate and contextually tailored, as this is crucial to foster multi-dimensional competencies that complement the specific disciplines of future health policy scholars. These scholars must possess the ability to genuinely serve their health systems towards achieving health-system goals and sustainable development.